2003
DOI: 10.1016/s0167-4889(02)00401-9
|View full text |Cite
|
Sign up to set email alerts
|

Platelet interaction with CNBr peptides from type II collagen via integrin α2β1

Abstract: Adhesion of blood platelets to fibrillar collagens plays a crucial role in haemostasis. Collagen type II is a homotrimeric member of the fibrillar collagen family, whose ability to interact with platelets has been poorly investigated. In this work, we analysed platelet adhesion to the whole collagen type II molecule, as well as to its CNBr peptides. We found that collagen type II is as efficient as collagen type I in supporting platelet adhesion. Platelet binding sites on collagen type II were identified in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…4,24,29 However, stimulation of PI3K␤ activity by integrin ␣2␤1 was also confirmed using a different specific ligand, the collagen-related peptide GFOGER. Moreover, although the majority of the experiments reported in this study were performed using type I monomeric collagen as an integrin ␣2␤1 ligand, many of the results have been confirmed in experiments with the GFOGER peptide (data not shown).…”
Section: Org Frommentioning
confidence: 90%
See 3 more Smart Citations
“…4,24,29 However, stimulation of PI3K␤ activity by integrin ␣2␤1 was also confirmed using a different specific ligand, the collagen-related peptide GFOGER. Moreover, although the majority of the experiments reported in this study were performed using type I monomeric collagen as an integrin ␣2␤1 ligand, many of the results have been confirmed in experiments with the GFOGER peptide (data not shown).…”
Section: Org Frommentioning
confidence: 90%
“…on May 11, 2018. by guest www.bloodjournal.org From Monomeric type I collagen has been mainly used in this study as a reliable, cheap, and easy-to-obtain ligand for integrin ␣2␤1, because previous studies have clearly demonstrated that under these conditions no activation of GPVI occurs. 4,24,29 However, stimulation of PI3K␤ activity by integrin ␣2␤1 was also confirmed using a different specific ligand, the collagen-related peptide GFOGER. Moreover, although the majority of the experiments reported in this study were performed using type I monomeric collagen as an integrin ␣2␤1 ligand, many of the results have been confirmed in experiments with the GFOGER peptide (data not shown).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…In contrast, the phenylalanine may be less important, since two other collagen type I ␣ 1 chain sequences, GLOGER and GASGER, were found to bind ␣ 1 I and ␣ 2 I, when I-domain-interacting areas were mapped within collagen by rotary shadowing (16). No other recognition sequences have been unequivocally identified hitherto, although collagens I and III contain 11 and 14 GER triple helical motifs respectively some of which occur within cyanogen bromide-cleaved peptides, which support integrin binding (17)(18)(19)(20)(21). One conserved sequence, GMOGER, is cleaved at methionine by cyanogen bromide, and so is not present in such peptides.…”
mentioning
confidence: 99%